Xylarinaps A–E, five pairs of naphthalenone derivatives with neuroprotective activities from Xylaria nigripes. (June 2021) - Li, Jing; Li, Lan-Qing; Long, Hong-Ping; Liu, Jian; Jiang, Yue-Ping; Xue, Ying; Wang, Wen-Xuan; Tan, Gui-Shan; Gong, Zhi-Cheng; Liu, Ji-Kai
Abstract: Five pairs of undescribed naphthalenone derivative enantiomers, xylarinaps A–E, including one pair of indole naphthalenones and four pairs of naphthalene-naphthalenone dimers, were isolated from the ethyl acetate extracts of the solid fermentation of Xylaria nigripes, which has been used as a traditional Chinese medicinal fungus for the treatment of insomnia, trauma, and depression. The structures of these enantiomers were elucidated based on comprehensive spectroscopic analysis, including NMR and HRESIMS. Their absolute configurations were assigned by the experimental and calculated ECD data. The neuroprotective effects of all the compounds against damage to PC12 cells by oxygen and glucose deprivation (OGD) were evaluated by an in vitro bioassay. The results revealed that xylarinaps A, B, D, and E significantly enhanced cell viability, decreased the levels of malondialdehyde (MDA), increased the levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), as well as further markedly inhibiting apoptosis, which indicated that these results could be the mode of action of their neuroprotective effect. Graphical abstract: Image 1 Highlights: Five pairs of undescribed naphthalenone derivative enantiomers were isolated from Xylaria nigripes. The structures of the enantiomers were assigned by spectroscopic and computational methods. Four compounds exhibited neuroprotective effects against oxygen and glucose deprivation-induced damage in PC12 cells.